國民小學多元文化族群學生學習困境脈絡下教師韌性與幸福感之研究 A Study of Teachers' Resilience and Well-being in the Context of the Learning Difficulties of Students from Multicultural Ethnic Groups in Elementary Schools - 張志瑋 Chih-Wei Chang (Shizi Peiyu Yu Jiaoshi Zhuanye Fazhan Qikan, 2025)
本研究旨在探究國民小學多元文化族群學生學習困境形成原因與因應策略、學生學習困境脈絡下之教師韌性與教師幸福感現況與關係。以個案研究紮根理論方法進行訪談、編碼和分析探究，選取新北市與桃園市國小教師計6校13人為對象。研究發現：一、多元文化族群學生學習困境脈絡下，教師因應韌性有：正向情緒管理、良好人際關係、情境與資源支持、提升專業成長、工作成就滿足以及良好親師溝通。二、教師提升幸福感策略有：善用成功經驗激勵、團隊合作與團隊支持、專業認同與專業提升、正向特質與使命感，以及不斷自我超越、反思。三、在多元文化族群學生學習困境下，提升教師韌性可讓個案教師感受到更多幸福感，而感受到較多幸福感的教師也通常呈現更高的教師韌性。 This study explores the causes of learning difficulties in and coping strategies of students from multicultural ethnic groups at national primary schools, as well as the current situation of and relationship between teachers’ resilience and well-being in this context. Thirteen teachers from six schools in New Taipei City and Taoyuan City were selected. The results showed that 1. in the context of learning difficulties faced by students from multicultural ethnic backgrounds, teachers’ resilience includes positive emotion management, strong interpersonal relationships, situational and resource support, professional growth, job satisfaction, and effective parent–teacher communication; 2. strategies for enhancing teachers’ well-being include leveraging successful experiences, fostering teamwork and support, strengthening professional identity and development, cultivating positive traits and a sense of mission, and engaging in continuous self-reflection and growth; and 3. improving teachers’ resilience can enhance their well-being and vice versa.